Penerapan Teknik Kripto-Kompresi Menggunakan Algoritma Columnar Transposition Cipher Dan Algoritma Rice Codes Dalam Mengamankan File Dokumen - Lestari, Dina (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
As technology advances, data and information security becomes increasingly important. Important data can be very easy to be hacked by parties who have no interest, if the data does not have a strong security system. Using cryptographic techniques alone can be said to be unsafe, because there are many applications that function to hack or decrypt data. Therefore, a stronger solution is needed to maintain the confidentiality of the data. To maintain the confidentiality of the data and overcome the increasingly sophisticated problem of data hacking, crypto-compression techniques have been developed as an effective solution. This technique combines two main components: encryption using the Columnar Transposition Cipher algorithm to secure messages, and compression using the Rice Codes algorithm to reduce file size. By combining the security of encryption and the efficiency of compression, this crypto-compression technique aims to produce a method that can maintain data confidentiality and reduce document file sizes significantly. The research results show that the crypto-compression technique for document files using the Columnar Transposition Cipher algorithm and the Rice Codes algorithm has succeeded in securing document files by creating a new file in .trc format and if the file is opened it cannot be opened and the results can be read. The process of returning the file in .trc format to a document file has also succeeded in returning to its original form completely.